A Novel Method of Selective Chromopertubation at Office Hysteroscopy - Peter Torok (Journal of Gynecological Research and Obstetrics - Peertechz Publications, 2016)
Introduction: Tubal dysfunction is diagnosed as an underlying cause of infertility in more than one third of cases. Laparoscopy dye is the gold standard procedure to detect tubal patency, but hysterosalpingography (HSG) and hystero-contrast-sonography (HyCoSy) is also used. Office hysteroscopy guided selective chromopertubation (OHSC-SPT) is a less invasive and reproducible method, which can be performed in an outpatient setting without anesthesia, therefore it can be carried out as an outpatient procedure.  Method: For the examination an office hysteroscope is used. A 1.7 mm diameter flexible plastic catheter is inserted through an inbuilt channel of the sheath. Normal saline is used for distention. The hysteroscope is introduced without grasping or dilatation of the cervix. First, diagnostic hysteroscopy is performed, then the catheter is inserted through the working channel and the tip of it is placed into the tubal orifice, through which methylene blue dye is injected slowly. If the tube is patent the blue dye does not appear in the uterine cavity and the normal color of the endometrium is seen. In case of tubal occlusion the distention media of the uterine cavity turns blue, due to the back-flow of the methylene blue.  Conclusion: After gathering additional experience the novel method of OHSC-SPT could be considered as an effective, minimally invasive method to investigate tubal patency, which can be performed in an office setting without anesthesia.